Time management in the life of a scholar - Dandago, Kabiru Isa (UUM Press, 2015)
Time management is a subject that concerns everybody: Male and female; rich and poor; young and old; leaders and followers; educated and uneducated; etc.It is a challenge that has to be faced squarely by everyone who is interested in accomplishing his/her tasks within the limited time available, and this time is equally endowed. This book is specifically focused on scholars, as role models for effective time management.These scholars could be at the primary school level, secondary school level, tertiary educational institutions (universities, polytechnics, colleges of education, etc.), research institutes/centers, etc.It is a challenge for them to lead other time users on effective management and utilization of time and also to go deep into research on various aspects of time management, so as to establish acceptable principles, models and theories on the subject matter.Although the book has the scholar in mind, other users of time in the various sectors of any economy would find this book very interesting and very useful.Good time management is the key factor to achieve so much more within the 24-hour-period endowed equally to mankind. Over the 24 years of his working life in the University, the authors has come to realist that most scholars in educational system and those in other levels of the educational sector are not according time management the attentions it deserves.The required attentions are: (i) in respect of its effective management to achieve desire results; and (ii) in respect of promoting it an a subject of study at various levels.This book is an attempt to address these two issues.